ONLINE OR OFFLINE EDUCATION. WHICH ONE IS MORE PREFERABLE? (Western European Journal of Linguistics and Education, 2024)
This article explores the comparative advantages and disadvantages of online and offline education methods, particularly in the context of the COVID-19 pandemic. Through a survey conducted among 105 graduates of UzSWLU, the study examines preferences and impacts on various aspects of student development, including time management, selfdiscipline, networking, and health